2009
DOI: 10.1007/s10404-008-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-based gas flow sensors

Abstract: Micro-electro-mechanical system (MEMS) devices integrate various mechanical elements, sensors, actuators, and electronics on a single silicon substrate in order to accomplish a multitude of different tasks in a diverse range of fields. The potential for device miniaturization made possible by MEMS micro-fabrication techniques has facilitated the development of many new applications, such as highly compact, non-invasive pressure sensors, accelerometers, gas sensors, etc. Besides their small physical footprint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 29 publications
1
66
0
Order By: Relevance
“…The introduction of MEMS (Micro-Electro-Mechanical Systems) technology allowed the fabrication of miniaturized flow sensors with unprecedented performance in terms of spatial resolution, response times, sensitivities, measurement range and power consumption. Integrated flow sensors have been largely investigated in last decades and literature reviews can be found in [1][2][3][4][5][6]. The wide majority of the proposed devices are based on a thermal principle.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of MEMS (Micro-Electro-Mechanical Systems) technology allowed the fabrication of miniaturized flow sensors with unprecedented performance in terms of spatial resolution, response times, sensitivities, measurement range and power consumption. Integrated flow sensors have been largely investigated in last decades and literature reviews can be found in [1][2][3][4][5][6]. The wide majority of the proposed devices are based on a thermal principle.…”
Section: Open Accessmentioning
confidence: 99%
“…Although differential temperature flow sensors have been widely investigated [1][2][3][4][5][6], very few works have been devoted to find the impact of the sensor structure and dimensions on the key figures of merit of the devices [14][15][16][17][18][19][20]. Fluid dynamic simulations provide useful indications on particular aspects of the sensor operation, but are unable to embrace the whole transduction process, involving different physical domains that altogether contribute to the sensor performance.…”
Section: Open Accessmentioning
confidence: 99%
“…These sensors complement technologies such as microfluidic channels, valves, pumps, and heaters that are assembled together to create so-called lab on a chip (LOC) devices or micro total analysis systems (µTAS). As such, there has been great interest in their development in the microelectromechanical systems (MEMS) community since the first micromachined thermal flow sensor in 1974 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They are also divided in subgroups. In an exhaustive and recent review, Wang et al [2] classified non-thermal flow sensors depending on the principle of measurement used: resonating, differential pressure-based, lift-force-based, and cantilever type flow sensors. A brief description of these working principles and a more detailed description of laser Doppler anemometry (LDA) will be provided.…”
Section: Non-thermal Flow Sensorsmentioning
confidence: 99%
“…Although often associated to silicon, because of its frequent use, its economical characteristics and its desirable mechanical properties, micromachining has been performed on several materials including metals, polymers and glasses. The concept of micro-electro-mechanical systems (MEMSs) is still considered to be an emerging technology, but it was born in the early sixties [2], and almost fourteen years (1974) passed until a milestone study appeared, describing the first integrated silicon-based sensor for gas flow measurement [3]. A high growth of research works in the field of MEMS and micromachined flow sensors took place in the eighties and about a decade was needed to develop the integration of many microfluidic devices into a single chip (e.g., micro pumps, valves and flow sensors).…”
Section: Introductionmentioning
confidence: 99%